Identification and molecular characterization of the complete genome of three viruses infecting lulo (Solanum quitoense) crops in Antioquia (Colombia) - Gallo, Yuliana; Toro, Luisa Fernanda; Jaramillo, Helena; Gutiérrez, Pablo Andrés; Marín, Mauricio (Sociedad Colombiana de Ciencias Hortícolas-SCCH and Universidad Pedagógica y Tecnológica de Colombia-UPTC, 2018)
Lulo is one the most promising crops in the Andean region of Colombia because of its unique organoleptic properties and potential for industrial processing. In Antioquia, there has been a marked increase of lulo plants exhibiting typical symptoms of viral diseases, such as interveinal yellowing, mosaics and sprout deformation. In this research, we studied the presence of viruses infecting lulo in bulked leaf samples from Eastern Antioquia. Viruses were detected using Next-generation sequencing (NGS), with confirmation by RT-PCR. The NGS resulted in a total of 10’777,822 paired-end reads, of which 40.4% corresponded to Cucumber mosaic virus (CMV), 0.09% to Potato yellow vein virus (PYVV) and 0.06% to Alstroemeria necrotic streak virus (ANSV). Complete genome sequences were obtained for each of these viruses. RT-PCR primers for CMV and ANSV detection were designed using the assembled genomes reported in this study. Future research should investigate the effect of these viruses on crop yield, plant longevity and seed quality as well as their means of transmission, host range and specific symptoms.